Mathematical modeling of a thermo-anemometric flow meter for measuring automotive diesel fuel consumption with an induction heating circuit - Y.O.; O.O. (Технічна інженерія, 2023)
The article investigates mathematical modeling of the induction heating element (IHE) at the base of the thermo-anemometric flow meter (TAFM) for measuring the flow of diesel fuel (DF). The consumption of DF is affected by many factors that can affect the accuracy of TAFM, namely fuel temperature, impurities and its viscosity. The heating element in the form of shadows, which was previously studied in the publication [1], is in contact with the fuel medium, which increases the risk of fuel ignition when a large current passes through it. In the induction TAFM, the heating is regulated by turning it on and off cyclically. The very process of heating DF in TAFM is based on the generation of induced electric currents inside the pipeline, which contributes to high efficiency, since heat is generated only where it is necessary and most importantly - does not come into contact with a flammable substance, such as DF. This process is helped by temperature sensors (thermocouple) included in the control system. For this purpose, a selected temperature mode is set for DF and TAFM, after heating the coolant to a certain temperature, it is automatically turned off, and after cooling, it is turned on again. According to a number of criteria, such as TAFM material with an induction heater, length, diameter and wall thickness of the TAFM pipeline, high-speed modes of fuel supply - the amount of energy with the appropriate voltage frequency supplied to two induction heating elements to maintain a constant temperature difference depending on from the volumetric fuel consumption Q. Based on the data of the simulated parameters of the voltage dependence (output signal of the flow meter) and the quantitative fuel consumption through the TAFM, it was determined that the level of the output signal is sufficient for measuring the fuel consumption in a wide range of values.